PENGGUNAAN LIMBAH CANGKANG TELUR SEBAGAI BAHAN PENGGANTI SEMEN DALAM BETON: SOLUSI BERKELANJUTAN UNTUK INDUSTRI KONSTRUKSI - Mukti, Sheala Aditya Kusuma; Sunarjono, Sri (Fakultas Teknik Universitas Palangka Raya, 2025)
In Indonesia, climate change is causing extreme weather and increasing natural disasters, affecting various aspects of life, including infrastructure. Concrete, as the main construction material in infrastructure development, has major environmental challenges due to the production of cement, which contributes significantly to greenhouse gas emissions. Therefore, efforts are needed to partially replace the use of cement with more environmentally friendly materials, one of which is the use of eggshell waste. Eggshells contain calcium carbonate (CaCO₃), which is chemically similar to materials such as lime and fly ash commonly used in concrete mixes. The purpose of this study is to analyze the effect of eggshell waste substitution on compressive strength and potential reduction in concrete production costs. Several variations of cement substitution with eggshell (0%, 2.5%, 5%, 7.5%, and 10%) were used in the production of concrete. This research uses an experimental approach with quantitative research methods. The results showed that the use of eggshell was maximum at 2.5%. From an economic point of view, the use of eggshell as a cement substitute can significantly reduce the cost of concrete production, especially at a replacement level of about 10%. This study provides recommendations for the use of eggshell waste in the construction industry as a more environmentally friendly and economical alternative, supporting the principle of circular economy and reducing the carbon footprint of concrete production. However, further research is needed to optimize the correct substitution dosage and improve the particle distribution in the concrete mix for more consistent results.